2007
DOI: 10.1091/mbc.e07-04-0391
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Up-Regulates Hypoxia-Inducible Factor-1α Transcription by Involving Phosphatidylinositol 3-Kinase and Nuclear Factor κB in Pulmonary Artery Smooth Muscle Cells

Abstract: The oxygen sensitive ␣-subunit of the hypoxia-inducible factor-1 (HIF-1) is a major trigger of the cellular response to hypoxia. Although the posttranslational regulation of HIF-1␣ by hypoxia is well known, its transcriptional regulation by hypoxia is still under debate. We, therefore, investigated the regulation of HIF-1␣ mRNA in response to hypoxia in pulmonary artery smooth muscle cells. Hypoxia rapidly enhanced HIF-1␣ mRNA levels and HIF-1␣ promoter activity. Furthermore, inhibition of the phosphatidylinos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
311
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(339 citation statements)
references
References 51 publications
26
311
1
1
Order By: Relevance
“…Thus, our results are in line with previous findings where Nab2 inhibited VEGF-induced tissue factor promoter activity (48). Recent studies have implicated cross-talk between NF-B and HIF-1␣ genes, where NF-B regulates HIF-1␣ promoter activity and mRNA expression in response to H 2 O 2 , short duration hypoxia, and TNF-␣ (20,21,50). Thus, the possibility of PlGF-mediated activation of HIF-1␣ through indirect stimulation of NF-B cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results are in line with previous findings where Nab2 inhibited VEGF-induced tissue factor promoter activity (48). Recent studies have implicated cross-talk between NF-B and HIF-1␣ genes, where NF-B regulates HIF-1␣ promoter activity and mRNA expression in response to H 2 O 2 , short duration hypoxia, and TNF-␣ (20,21,50). Thus, the possibility of PlGF-mediated activation of HIF-1␣ through indirect stimulation of NF-B cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Crosstalk between the HIF and NF!B pathways has been demonstrated by a number of in vitro and in vivo studies showing that NF!B plays an important role in regulating basal and stimulated HIF-1# expression [7,[15][16][17][18]. NF!B can also regulate HIF-2# signalling through an interaction with the NF!B essential modulator (NEMO), which aids in the recruitment of transcriptional co-activators such as CREB binding protein (CBP) and p300, and increases HIF-2# transcriptional activity [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, defining the relationship between NF-kB and HIF-1a has proven elusive. Using in vitro systems, it was reported that HIF-1a activates NF-kB 9 , that NF-kB controls HIF-1a transcription 10 and that HIF-1a activation may be concurrent with inhibition of NF-kB 11 . Here we show, with the use of mice lacking IKK-b in different cell types, that NF-kB is a critical transcriptional activator of HIF-1a and that basal NF-kB activity is required for HIF-1a protein accumulation under hypoxia in cultured cells and in the liver and brain of hypoxic animals.…”
mentioning
confidence: 99%